EDUKASI KESEHATAN FAKTOR PENYEBAB HIPERTENSI DUSUN I MADYO DESA SIDODADI, KECAMATAN SIBIRU-BIRU, KABUPATEN DELI SERDANG - Novrika Silalahi; Pitto Pratiwi Malau; Ana Apriana; Bachtiyar Wahab; Sulastri Br Ginting (INSTITUT KESEHATAN DELI HUSADA, 2023)
Hypertension is high blood pressure of a long duration with blood pressure exceeding ≥ 140/90 mmHg, in general normal blood pressure is 120/80 mmHg. Symptoms that appear in hypertension are headaches, nausea, fatigue, vomiting, shortness of breath, anxiety, blurred vision which occurs due to damage to the brain, eyes, heart and kidneys. Many people do not fully understand the symptoms of hypertension. With the target organ in the brain being stroke, hypertension is the main cause of stroke which carries a high death rate. Hypertension is an important factor that triggers non-communicable diseases such as heart disease. Hamlet I Sidodadi Village receives a monthly report from the local health service's health research that hypertension is the biggest disease problem. This extension education began with a location survey in Sidodadi Village, Sibiru-Biru District, Deli Serdang Regency, so that data was obtained on 232 KK. And the results of educational outreach activities through discussions and questions and answers of ongoing outreach activities, it was found that 57 residents or 95% experienced an increase in hypertension and how to prevent hypertension. It was obtained from the results of the counseling that the occurrence of hypertension was caused by 3 main factors, namely that the dominant residents of Sidodadi Village, Sibiru-Biru District had a smoking habit, there were still many residents who consumed excessive salt, and the dominant age of the residents was over 40 years, classified as susceptible to hypertension.